Tax competition, relative performance and policy imitation - Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2009)
Rather than about absolute payoffs, governments in fiscal competition often seem to care about their performance relative to other governments. Moreover, they often appear to mimic policies observed elsewhere. We study such behaviour in a tax competition game with mobile capital à la Zodrow-Mieszkowski. Both with relative payoff concerns and for imitative policies, evolutionary stability is the appropriate solution concept. It renders tax competition more aggressive than with best-reply policies (Nash equilibrium). Whatever the number of jurisdictions involved, an evolutionary stable tax policy coincides with the competitive outcome of a tax competition game played among infinitely many governments. Tax competition among boundedly rational governments, thus, involves drastic efficiency losses.
Keywords: H77; H75; C73; 330; fiscal competition; relative performance; tax mimicking; evolutionary stability; Steuerwettbewerb; Imitationswettbewerb; Beschränkte Rationalität; Evolutionäre Spieltheorie; Wohlfahrtseffekt; Theorie